AG-ZSM-11 ZEOLITE SYNTHESIS USING SILICA FROM ELEPHANT GRASS FOR LED APPLICATION - Sundari, Citra D. D.; Setiadji, Soni; Firmansyah, Atthar Luqman; Abdurahman, Dede; Nurbaeti, Denia Febby (Walisongo Journal of Chemistry, 2018)
Silica (SiO2) has been successfully isolated from elephant grass by the sol gel method through pH regulation using NaOH and HCl. The resulting silica has an amorphous character with crystalline phase impurities. The isolated silica was then used as a source of silica for the synthesis of ZSM-11 zeolite using the hydrothermal method with a ratio of SiO2 : TBAOH : H2O = 1 : 0.35 : 25. XRD characterization results confirmed the formation of ZSM-11 zeolite. The SEM results show that the ZSM-11 zeolite crystal morphology is oval with crystal growth in all directions. Immersion of the synthesized ZSM-11 zeolite into AgNO3 solution and followed by calcination resulted in zeolite Ag-ZSM-11 which has different optical properties compared to the initial ZSM-11 zeolite. Zeolite ZSM-11 gives purple luminescence while zeolite Ag-ZSM-11 gives pink luminescence when illuminated under UV lights